Participation and engagement of a rural community in Ciclovía: progressing from research intervention to community adoption - Linda K. Ko; Eligio Jimenez; Oralia Cisneros; Emily V. R. Brown; Genoveva Ibarra; Sonia Bishop; Monica Escareño; Luis Serrano-Rubio; Eileen Rillamas-Sun; Jason A. Mendoza; Sarah Sutton (BMC, 2021)
Abstract Background Open streets events, where roads are temporarily closed to motorized vehicles, can provide safe spaces for physical activity (PA) and become sustainable community infrastructure. Since 2016, we have collaborated with a rural community to implement an open streets event, named ciclovía. In 2019, ciclovía was adopted as a community-wide program. This paper describes the process of building and progressing a ciclovía from a research intervention to a community-adopted program and participation of a rural community in ciclovía. Methods We used community-based participatory research to foster bidirectional learning on how to optimize the content and implementation of ciclovía to be feasible and acceptable for rural communities. The community-academic partnership focused on: 1) understanding the science of ciclovía; 2) learning the implementation process; 3) creating tools to facilitate planning, implementation, and evaluation of ciclovía; and 4) developing transition steps from a research intervention to a community-adopted program. Results The progression of the research intervention to community adoption spanned 2 years. First, the partnership met quarterly to discuss the science of ciclovía, its utility, and its adaptation for rural communities. Second, the partnership studied processes that facilitated ciclovía implementation. Third, the partnership created the ciclovía planning guide and tools for communities to establish their own ciclovía. The guide included forming a planning committee, setting meeting and communication plans, marketing and promotion, and selecting evaluation tools. Fourth, the transition steps from research intervention to community adoption included creating roles and responsibilities, implementing ciclovía using the planning guide, and convening listening sessions for improvement on implementation. Community attendance at ciclovía doubled from 189 individuals (126 children and 63 adults) when it was a research intervention to 394 individuals (277 children and 117 adults) when it was a community program. Conclusions The progression from a research intervention to a community-adopted program encompasses multiple steps that involve bidirectional learning and partnership with the community. Lessons learned from this study are integrated into a disseminatable ciclovía planning guide.